2004
DOI: 10.1007/s00701-004-0308-2
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured de novo intracranial aneurysms

Abstract: For not only young but also elder patients with a treated aneurysm (from the fifth decade to the sixth), especially for women, late angiography or alternative modalities of less-invasive examination should be considered. To detect de novo intracranial aneurysms before rupture, the search for a de novo aneurysm should be performed within 6.39 years after a previous examination that shows an aneurysm to be nonexistent, in view of the 95% confidence interval of the mean time to de novo aneurysmal rupture (6.39-15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 19 publications
0
12
0
2
Order By: Relevance
“…9 In our series, the earliest symptomatic recurrent aneurysm (with epileptic seizure) was found 6 years after the initial treatment, and the first de novo aneurysms (with SAH) at 11 years after SAH in concordance with reported adult series. 3,13 One pediatric series of 26 patients with angiographic follow-up reported the earliest recurrent and de novo aneurysms at a short-term interval of 5 months, 5 whereas another at 5 years. Among adult series, a short-term angiographic follow-up at 3-to 5-year intervals was recommended in patients aged <50 years with hypertension, 14 whereas another study suggested imaging for female patients at 10 years after the initial aneurysm treatment.…”
Section: When and Whom To Follow-upmentioning
confidence: 99%
“…9 In our series, the earliest symptomatic recurrent aneurysm (with epileptic seizure) was found 6 years after the initial treatment, and the first de novo aneurysms (with SAH) at 11 years after SAH in concordance with reported adult series. 3,13 One pediatric series of 26 patients with angiographic follow-up reported the earliest recurrent and de novo aneurysms at a short-term interval of 5 months, 5 whereas another at 5 years. Among adult series, a short-term angiographic follow-up at 3-to 5-year intervals was recommended in patients aged <50 years with hypertension, 14 whereas another study suggested imaging for female patients at 10 years after the initial aneurysm treatment.…”
Section: When and Whom To Follow-upmentioning
confidence: 99%
“…Although aneurysm growth has been suggested to be erratic, 12 existing models of aneurysm screening or treatment generally incorporate a constant time-independent growth rate and risk of rupture. Aneurysms that grow fast in a short period of time [14][15][16]30,31 are likely to have high risks of rupture for short periods of time. 11 Variable growth rates with corresponding time-variable risks of rupture will change predictions of the SAH risk over different time intervals.…”
mentioning
confidence: 99%
“…Although the postoperative course was uneventful, de novo aneurysm could be formed due to the hemodynamic change after successful treatment. 9) As a result, she will be regularly followed up at the outpatient clinic.…”
Section: Discussionmentioning
confidence: 99%